Isolated Splenic Infarction: An Initial Manifestation of Postoperative Atrial Fibrillation - Chaitra Janga MD; Kimberley Okoyeze MD; Vincent Chan MD (SAGE Publishing, 2022)
Splenic infarction is an uncommon cause of abdominal pain. In this article, we present a case of isolated splenic infarction presenting with severe abdominal pain, nausea, and with associated generalized weakness. Computed tomography (CT) abdomen and pelvis with contrast revealed multiple splenic infarctions of the entire lower pole with occlusion of the branch splenic arteries, while CT abdomen without contrast was unremarkable. Etiology was later revealed to be thromboembolism secondary to atrial fibrillation. It was managed with anticoagulation. To our knowledge, this is the second case of splenic infarction presenting as an initial manifestation of atrial fibrillation (AF), reported in the literature.